The Stages of Self-Disclosure by Anonymous Chat Users in Telegram to Build Virtual Relationships - Sevia Hasanah; Khaerudin Imawan (Salus Publica: Journal of Community Service, 2026)
The development of technology creates the new form of interpersonal relation, which is known as virtual relationship. Building online relationship is widely used by people especially young people. The phenomenon of building virtual relationship tends to make friendship or girl/boyfriend through the feature of Telegram, Anonymous Chat. However, this feature also vulnerable to digital sexual harassment and data privacy because this feature is anonymous. This research is intended to describe and analyses the phenomenon of self-disclosure in building virtual relationship through anonymous chat feature in Telegram. This study employs descriptive approach with in-depth interview with five informants who have experienced virtual relationship through the media. The findings of the research show that all informants have experienced the stages of self-disclosure as it is explained by social penetration theory, starting from orientation to stable exchange. In the initial stage, informants tended to disclose general and secure information as a form of caution in an anonymous space. As interactions and trust developed, informants began to reveal more personal information, including emotional experiences and true identities, although still with selectivity. These findings suggest that anonymity does not always hinder self-disclosure, but rather can be a springboard for developing closeness if managed carefully and with positive communication. This study also found that self-disclosure with strangers is easier than with someone within one's social circle.